Predictors of Attitude towards Advertisements among Urban Consumers in Malaysia - Rajesh Kumar, Sodarshan Kumar (2023)
The purpose of the present study is to understand how Malaysian consumers respond in terms of attitude to advertisement to advertisements using sexual content or nudity. Past studies drew mixed results in terms of favourable and unfavourable response to attitude to advertisement, gender and culture when advertisements used sexual content. Content analysis to advertisement with sexual content or nudity is important to determine to what extent this effects consumer response in terms of attitude to advertisement. If the nudity or sex appeal used evokes positive attitude to advertisement than such use should be adopted. In adopting this approach marketer increase the opportunity in evoking positive attitude that subsequently results in more positive perception of brand and purchase intent. This study examination of factors influencing consumer evalution in terms of attitude to advertisement using sexual content or nudity, by employing three factor theory of emotion or stimulus organism response theory, basic human value theory, evolutionary theory and bioinformational theory. This study employed a quantitative approach to examine consumer response and data was collected via questionnaire survey from working adults living in the Klang Valley. Data analysis was conducted using SPSS software and Smart PLS version 4. According to the study's findings, attitudes towards advertisements and perceived nudity are negatively correlated. Only arousal mediated between perceived nudity and attitude to advertisement while the association between perceived nudity and attitude towards advertisements was not mediated by pleasure. Additionally, gender moderated the paths between perceived nudity and arousal, between perceived nudity and pleasure; between arousal and attitude; and between pleasure and attitude. From the 14 hypothesis developed for this study, a total of 10 hypotheses were supported, resulting in a number of theoretical and practical contributions.